A flicker in the dark - Willingham, Stacy (New York : Minotaur Books, 2022)
When Chloe Davis was twelve, six teenage girls went missing in her small Louisiana town. By the end of the summer, her own father had confessed to the crimes and was put away for life. Now twenty years later, Chloe is a psychologist in Baton Rouge and getting ready for her wedding. When a local teenage girl goes missing, and then another, that terrifying summer comes crashing back.
Keywords: Missing persons -- Fiction; Fathers and daughters -- Fiction; Psychologists -- Fiction; Baton Rouge (La.) -- Fiction; Thrillers (Fiction); Psychological fiction